Application of Deep Breathing and Pillow-Hitting Techniques and Mozart Classical Music Therapy on the Ability to Control Violent Behavior in the Gatotkaca Ward of Dr. Amino Gondohutomo Mental Hospital, Central Java - Feki Karu; Dwi Indah iswanti (BIOSAINSTEK, 2026)
Violent behavior can be divided into low and high levels. At a low level, violent behavior can be seen as hostility. While at a high level, violent behavior can cause serious and dangerous injuries (Suryanti & Ariani, 2018). To describe the application of Deep Breathing and Hitting a Pillow and Mozart Classical Music Therapy on the Ability to Control Violent Behavior in Nursing Care. This case study involved three patients (Mr. I, Mr. S, and Mr. O) who showed symptoms of Risk of Violent Behavior. A nursing implementation was carried out for five days for patient Mr. I, (May 29-June 2, 2025), patient Mr. S (June 3-7, 2025), while for Mr. O (June 8-12, 2025). Through a gradual approach, namely the Deep Breathing technique, hitting a Pillow, and Mozart Classical Music Therapy, and input of the techniques taught into the patient's daily schedule. Data analysis used was frequency distribution and percentage. There was a significant decrease in the verbalization indicator of the ability to control the risk of violent behavior. The scores of all three patients decreased from "increased" with a percentage value of 100.0% on the first day to "decreased" with a percentage value of 100.0% on the third day, indicating the effectiveness of the interventions provided to the patients. Deep breathing, pillow beating, and Mozart classical music therapy have been proven effective in reducing the intensity and frequency of violent behavior in patients with potential violent behavior care problems. These actions can be used as for non-medication therapy options in psychiatric care settings.